Sociaal Engagement in de Kunst 1850-1950. - Bafcop, M.; Courcelles, Pierre; Frérot, Christine; Goldmann, Jean; Melot, Michel; Vanroy, J.; Cultureel Centrum Burgemeester A. Spinoy, Mechelen (Mechelen : Stad Mechelen, 1982)
Brockdorff, Victor ; Brouwers, Rik ; Chagall, Marc ; Claus, Emile ; Courbet, Gustave ; Cremonini, Leonardo ; De Bruyne, Gustaaf ; Dix, Otto ; Eigenberger, Robert ; Ekeland, Arne ; Ensor, James ; Eyckermans, Lode ; Fautrier, Jean ; Fuchs, Ernst ; Gotsch, Friedrich Karl ; Gris, Juan ; Guttuso, Renato ; Kokoschka, Oskar ; Leger, Fernand ; Moore, Henry ; Munch, Edvard ; Pechstein, Max ; Permeke, Constant ; Piignon, Edouard ; Schiele, Egon ; Somville, Roger ; Spilliaert, Léon
Bijlage: Franse vertaling
biografie
Sociaal Engagement in de Kunst 1850-1950, Cultureel Centrum Burgemeester A. Spinoy, Mechelen, 26 september - 21 november 1982
Nederlands
boek